Role of collisionality and radiative cooling in supersonic plasma jet collisions of different materials - Collins, GW; Valenzuela, JC; Speliotopoulos, CA; Aybar, N; Conti, F; Beg, FN; Tzeferacos, P; Khiar, B; Bott, AFA; Gregori, G (American Physical Society, 2020)
Currently there is considerable interest in creating scalable laboratory plasmas to study the mechanisms behind the formation and evolution of astrophysical phenomena such as Herbig-Haro objects and supernova remnants. Laboratory-scaled experiments can provide a well diagnosed and repeatable supplement to direct observations of these extraterrestrial objects if they meet similarity criteria demonstrating that the same physics govern both systems. Here, we present a study on the role of collision and cooling rates on shock formation using colliding jets from opposed conical wire arrays on a compact pulsed-power driver. These diverse conditions were achieved by changing the wire material feeding the jets, since the ion-ion mean free path (λmfp-ii) and radiative cooling rates (Prad) increase with atomic number. Low Z carbon flows produced smooth, temporally stable shocks. Weakly collisional, moderately cooled aluminum flows produced strong shocks that developed signs of thermal condensation instabilities and turbulence. Weakly collisional, strongly cooled copper flows collided to form thin shocks that developed inconsistently and fragmented. Effectively collisionless, strongly cooled tungsten flows interpenetrated, producing long axial density perturbations.